2019
DOI: 10.1177/1948550619875150
|View full text |Cite
|
Sign up to set email alerts
|

School Deferred: When Bias Affects School Leaders

Abstract: In the classroom, Black students are disciplined more frequently and more severely for the same misbehaviors as White students. Though teachers have influence over disciplinary actions, the final decisions for exclusionary discipline (i.e., suspensions and expulsions) are principals’ responsibility. We test how principals make disciplinary decisions in a preregistered experiment. Principals endorsed more severe discipline for Black students compared with White students across two time points. Further, this dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Research indicates that a variety of factors contribute to the school-to-prison pipeline. Some studies indicate that school personnel may be biased in the ways they respond to Black students [11,12]. The lack of teacher preparation and support has been documented to be one of the contributing factors as well [13,14].…”
Section: Factors Contributing To the School-to-prison Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that a variety of factors contribute to the school-to-prison pipeline. Some studies indicate that school personnel may be biased in the ways they respond to Black students [11,12]. The lack of teacher preparation and support has been documented to be one of the contributing factors as well [13,14].…”
Section: Factors Contributing To the School-to-prison Pipelinementioning
confidence: 99%
“…The researchers found that Black students had a higher chance of being labeled troublemakers than White students for participating in the same behavior. They suggested that future efforts to reduce the school-to-prison pipeline need to focus on principals since they are the ones making the final decisions on suspensions and expulsions [12].…”
Section: Biased School Personnelmentioning
confidence: 99%
“…Even at the psychological level, the attitudes, perceptions, and beliefs of myriad others influence students' academic outcomes. School administrators are often responsible for final decisions on matters such as academic placement and discipline, and research shows that principals [96] and school counselors [97] can exhibit racial bias in these decisions even with no input from teachers. Parents may be differentially likely to recognize the potential of their children and advocate for advanced placement [98], perhaps in part due to psychological factors such as their own biases (e.g., gender stereotypes [99]) or cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…The study, which was based in the United States, comprised a sample of public middle and high school assistant principals across two misbehaviors. Jarvis and Okonofua (2020) found that the school principals "endorsed more severe discipline for Black students after the second misbehavior compared with White students. Because misbehaviors were held constant, we can conclude it is due to the student's perceived race and not aspects of the misbehavior" (p. 496).…”
Section: Streaming and Biased Notions Of Achievementmentioning
confidence: 97%